2010
DOI: 10.1149/1.3384665
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of La[sub 0.6]Ca[sub 0.4]Co[sub 0.8]Ru[sub 0.2]O[sub 3] for Oxygen Reduction Reaction in an Alkaline Electrolyte

Abstract: We employed an amorphous citrate precursor ͑ACP͒ method to synthesize stoichiometric La 0.6 Ca 0.4 Co 0.8 Ru 0.2 O 3 powders. Result from X-ray diffraction demonstrated a perovskite La 0.6 Ca 0.4 CoO 3 lattice, indicating the incorporation of Ru 3+ at the Co 3+ sites. Image from the scanning electron microscope revealed a foamlike microstructure with various pores at 0.5-3 m. La 0.6 Ca 0.4 Co 0.8 Ru 0.2 O 3 exhibited a higher H 2 O 2 decomposition rate in KOH solution as opposed to that of ACP-derived La 0.6 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…This strategy of enhancing the catalytic activity of the noble metal was also reported by other groups (e.g. Ir or Ru‐doped La 0.6 Ca 0.4 CoO 3 and Ru‐doped CaMnO 3 ) …”
Section: Perovskite Materials For Energy‐related Applicationssupporting
confidence: 79%
See 1 more Smart Citation
“…This strategy of enhancing the catalytic activity of the noble metal was also reported by other groups (e.g. Ir or Ru‐doped La 0.6 Ca 0.4 CoO 3 and Ru‐doped CaMnO 3 ) …”
Section: Perovskite Materials For Energy‐related Applicationssupporting
confidence: 79%
“…Owing to their low cost, high efficiency and flexible structures, perovskite oxides have recently drawn tremendous attention as promising alternatives to high‐efficiency OER electrocatalysis in alkaline media . Most notably, BSCF, which was formerly known as a high‐performance perovskite in oxygen permeation membranes and SOFCs, has been identified by Shao‐Horn and co‐workers as a highly active OER catalyst that even outperforms the gold‐standard IrO 2 in terms of intrinsic activity .…”
Section: Perovskite Materials For Energy‐related Applicationsmentioning
confidence: 99%
“…In the series of La 0.8 Sr 0.2 Co 1– y B′ y O 3 (B′ = Cu, Ni, Fe, and Cr), the authors found that La 0.8 Sr 0.2 Co 0.9 Ni 0.1 O 3 and La 0.8 Sr 0.2 Co 0.9 Fe 0.1 O 3 showed the highest electrocatalytic activity in 1 M KOH solution, whereas the partial substitution of Co with Cu or Cr exhibited detrimental effects on the electrocatalytic activity . Doping with precious metals can also lead to synergistic effects that improve electrocatalytic activities (e.g., the incorporation of Ir into La 0.6 Ca 0.4 CoO 3 to form La 0.6 Ca 0.4 Co 0.8 Ir 0.2 O 3 and Ru-doped La 0.6 Ca 0.4 CoO 3 with the composition of La 0.6 Ca 0.4 Co 0.8 Ru 0.2 O 3 ); however, the high cost of these elements has hindered this development.…”
Section: Abo3‑δ Perovskite-type Catalystsmentioning
confidence: 99%
“…Further work led to catalyst materials of the general composition La 1Àx A x Co 1Ày B y O 3 (A = Ca; B = Mn, Fe, Co, Ni, Cu) synthesized by the different methods. [148][149][150][151][152][153][154][155][156] A strong composition dependence on catalyst performance was observed for both A and B-site doping. For example, Sr-substitution showed better performance at oxygen evolution, whereas, the Ca substituted material showed slightly better performance upon oxygen reduction.…”
mentioning
confidence: 99%